Molecular strategies in the treatment of skin cancers - Włodarkiewicz, Adam; Sobjanek, Michał; Michajłowski, Igor; Nałęcz, Dariusz; Niekra, Marcin; Michajłowski, Dymitr (Dermatology Review/Przegląd Dermatologiczny, 2012)
Non-melanoma skin cancers (NMSC) are the most frequent malignant neoplasms in Caucasians, presenting constantly increasing frequency and morbidity. Surgical excision remains the gold standard in the treatment of NMSC. The discovery of molecular pathways of cell growth and differentiation, apoptosis and invasion enables the introduction of molecularly guided therapies of skin cancer. The most thoroughly investigated signalling pathways are the epidermal growth factor receptor (EGFR) pathway and hedgehog pathway. We present an overview of the mechanisms of both signalling pathways and their significance in the development and treatment of skin cancers. The data indicate that EGFR plays a significant role in skin carcinogenesis and its inhibitors may be potentially utilized in growth reduction of advanced tumors inappropriate for surgical treatment. Disturbance in the hedgehog pathway, attributed to UVR-dependent PATCHED gene mutations, plays an important role in the development of NMSC.